Development of Scientific-Based Newton's Law Teaching Aids Using Arduino Uno Microcontroller - Lenisa, Stefiana; Azizahwati, Azizahwati; Irawan, Dedi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research is intended to develop Newton's law teaching aids to understand Newton's law material in high school. In this study, validation process was carried out by three expert lecturers i.e. expert in the media field, expert in the material field, and expert in the pedagogic field. The data collection technique was carried out by providing a validation questionnaire in the form of a checklist. After that, the collected data were than analyzed using descriptive analysis by calculating the average of each indicator used to determine the validity of Newton's law teaching aids and the developed guidebook. The results of the study stated that the teaching aids and guidebooks on Newton's law materials developed were valid at a very satisfactory level. Therefore it can be concluded that Newton's law teaching aids have been successfully developed and can be used in the learning process.Keywords: newton's law, teaching aids, arduino uno, microcontroller.